1997
DOI: 10.1002/(sici)1096-9861(19971006)386:4<613::aid-cne7>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic plasticity of 5‐hydroxytryptamine–immunoreactive terminals in the phrenic nucleus following spinal cord injury: A quantitative electron microscopic analysis

Abstract: The present study was conducted to examine the plasticity of 5-hydroxytryptamine (5-HT)-immunoreactive terminals in the rat phrenic nucleus following an ipsilateral C2 spinal cord hemisection and 30-day survival period. A retrograde horseradish peroxidase (HRP) labeling technique was used to identify the phrenic motoneurons at the electron microscopic (EM) level. After employing a pre-embedding immunocytochemical technique, the ultrastructural characteristics of 5-HT-immunoreactive terminals were qualitatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Double synapses, defined as axon terminals forming synaptic contacts with two different postsynaptic profiles (Tai et al, 1997) were observed on both the control (n ϭ 2), and experimental (n ϭ 3) sides. Ipsilaterally, three boutons were of the M-type and 25 of the S-type, while the corresponding numbers for the contralateral side were 2 and 22, respectively.…”
Section: Individual Hrp-labeled Primary Afferent Boutonsmentioning
confidence: 99%
“…Double synapses, defined as axon terminals forming synaptic contacts with two different postsynaptic profiles (Tai et al, 1997) were observed on both the control (n ϭ 2), and experimental (n ϭ 3) sides. Ipsilaterally, three boutons were of the M-type and 25 of the S-type, while the corresponding numbers for the contralateral side were 2 and 22, respectively.…”
Section: Individual Hrp-labeled Primary Afferent Boutonsmentioning
confidence: 99%
“…These influences on respiration are mediated both directly through serotoninergic projections to respiratory motoneurons (Holtman et al, 1984; Pilowsky et al, 1990; Tai et al, 1997) and indirectly via serotoninergic inputs to the brainstem respiratory groups (Connelly et al, 1989; Cream et al, 2002; Lalley et al, 1994; 1995; Mulkey et al, 2007; Voss et al, 1990). There is evidence that medullary serotonin-containing neurons serve as central chemoreceptors (Bernard et al, 1996; Li et al, 2006a; Messier et al, 2002; 2004; Nattie, 1999; 2001; Nattie and Li, 2001; Nucci et al, 2008; Penatti et al, 2006; Taylor et al, 2004; 2005; 2006), mediate long-term facilitation of respiratory motor output following episodic hypoxia or electrical stimulation of carotid chemoafferent neurons (Fuller et al, 2000; 2001; Ling et al, 2001; Millhorn et al, 1980; Millhorn, 1986; Mitchell et al, 2001), and are necessary for recovery of respiratory activity following upper cervical spinal injury (Fuller et al, 2005; Tai et al, 1997; Zhou and Goshgarian, 1999; 2000; Zimmer and Goshgarian, 2006). Furthermore, neurons near the medullary midline in felines have been shown to participate in eliciting cough (Baekey et al, 2003; Jakus et al, 1998) and emesis (Miller et al, 1996), although it is unknown whether these cells contain serotonin.…”
Section: Introductionmentioning
confidence: 99%
“…Following upper cervical lateral hemisection, and interruption of inspiratory drive on one side of the spinal cord, the ipsilateral hemiparetic diaphragm spontaneously regains function following contralateral phrenic nerve transection. This injury-induced respiratory plasticity occurs via activation of pre-existing crossed pathways within the spinal cord (Goshgarian and Guth, 1977; Guth, 1976) and is largely serotonin dependent (Hadley et al, 1999; Tai et al, 1997). To our knowledge, only one paper has assessed respiratory function following incomplete experimental thoracic injuries.…”
Section: Discussionmentioning
confidence: 99%